Analyzing the Impact of Loop Parameter Variations on the Transient Response of Second Order Voltage-Switched CP-PLL - Ali, E.; Narwani, D.; Bughio, A. M.; Nizamani, N.; Siyal, S. H.; Khatri, A. R. (Engineering, Technology & Applied Science Research, 2021)
The analysis of the behavior of Charge Pump Phase-Locked Loop (CP-PLL) is a challenging task due to its mixed-signal architecture. Out of its two types, i.e. Current Switched CP-PLL (CSCP-PLL) and Voltage Switched CP-PLL (VSCP-PLL), the prior produces symmetrical pump currents, resulting in an appropriate transient performance to be analyzed. The loop parameters are important to set the gain, target frequency, and assure the stability of the system. The more important is the bandwidth of the loop, which is dependent on the loop filter parameters to perform stable operation and locking time. In this paper, the impact of loop parameter variations on the overall transient behavior of the system is investigated. It has been shown that loop parameters play an important role to ease the design of mixed-signal PLLs.